MOOD AND MODALITY SYSTEMS REALIZED IN EFL TEACHER-STUDENTS CLASSROOM INTERACTION DURING DAILY ASSESSMENT - Sri Asti Ramdhani; Andi Rustandi (Jurnal Siliwangi: Seri Pendidikan, 2018)
This study aimed at investigating the relationship between the teacher and her students which is revealed in the classroom interaction and investigating the implication of Mood and Modality towards language learning. Mood and Modality systems which relate to the interpersonal meaning could reveal the role and relationship between the interactants (Eggins and Slade, 1997, p. 49). This study employed qualitative discourse analysis to analyze the data which were recorded by the writer into Mood types, Modality system, frequent Subject choice, and speech function. The participants in this study were the teacher and her students of 10th and 11th grade of a senior high school in Ciamis. The results of this study showed that the teacher played her role as information giver. Besides, the teacher also showed her authority to lead the classroom activities by producing imperative clause. Furthermore, this study could improve the EFL students’ speaking skill and critical thinking by interacting with their teacher in the academic setting at which academic setting was a good place to learn and practice the grammatical English.